The gardens and environment renewal of the Benedictine Abbey in Tihany - Herczeg, Ágnes (4D Journal of Landscape Architecture and Garden Art, 2006)
The Benedictine Abbey in Tihany celebrated the 950 year's formation anniversary of in the year of 2005. Along with the renovation work of abbey’s church and monastic quarters, the Abbey garden reconstruction were finished before fór the celebration ceremony.The cloister, the Southern garden, the 'Rege' yard, the front square of the church and the monastic quarters were designed. During the planning and implementation work, we took in consideration the benedictine spiritual heritage, tradition, the landscape connections and art relic principles.
Keywords: Tihany; Benedictine Abbey in Tihany; garden reconstruction